Dental Anomalies and Gender Dimorphism in Tooth Size of Malay Patients - Bunyarit, SS; Asma, AAA; Rahman, NA Abdul; Adri, SS; Rahman, MM (Bangladesh Journal of Medical Science, 2017)
Objectives: To determine the prevalence of dental anomalies, sexual dimorphism and antimere differences of tooth size of Malay in Malaysia. Methods: Orthodontic patients for the years 2008-2010 were selected. Among these two hundred patients were selected based on file records. Their panoramic radiographs were examined. The prevalence of various dental anomalies was determined. Mesiodistal and buccolingual diameters of the teeth were measured using electronic calipers with accuracy of up to 0.01mm. Analysis was carried out using SPSS statistical package version 18.0 (2009). Results: In the Malay patients the frequency of hypodontia was 7.5%, followed by hyperdontia (2%), microdontia, dens evaginatus and short root were 1%, respectively. In addition, their macrodontia, germination and dilaceration were 0.5% , while the remaining 86% did not display any dental anomalies. This study demonstrated greater tooth sizes in male compared to female subjects except for buccolingual site of upper canine and lower incisors. Greatest dimorphism in mesiodistal dimension was noted in the lower canine while buccolingual dimension was presented by upper lateral incisor. It was found that there was no significant difference (P>0.05) in tooth measurements for right and left antimeres observed for the majority of tooth classes. Conclusion: In the Malay subjects, hypodontia was the commonest dental anomaly. The Malay males had greater tooth sizes than their female counterparts. There were almost no significant antimere differences in tooth sizes. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.115-121